In This Together Teachers' Experiences with Transnational, Telecollaborative Language Learning Projects - Dooly Owenby, Melinda Ann; O'Dowd, Robert (Telecollaboration in Education, 2018)
This book provides a nexus between research and practice through teachers' narratives of their experiences with telecollaboration. The book begins with a chapter outlining the pedagogical and theoretical underpinnings of telecollaboration (also known as Virtual Exchange), followed by eight chapters that explain telecollaborative project design, materials and activities as well as frank discussions of obstacles met and resolved during the project implementation. The projects described in the volume serve as excellent examples for any teacher or education stakeholder interested in setting up their own telecollaborative exchange.